Women's education in Islam - Ulfatillaeva Sayyora Sobirjon kizi (Ethiopian International Journal of Multidisciplinary Research, 2023)
Islam has created all the conditions for women to maintain their dignity, to maintain their femininity, and to serve their communities, their homeland, and their religion through the full performance of their feminine duties and The Quran as well as the hadith leave no doubt that women, like men, are obligated to increase their knowledge and pursue it